Depresión asociada a deterioro cognitivo en adultos mayores del Centro Gerontológico Nuevo Amanecer de la ciudad de Zumba - Guevara Castillo, Jefferson Rolando (2022)
Depression is a pathology with high prevalence in all populations, especially in older adults, who do not receive adequate attention for diagnosis and treatment, and has been associated with cognitive impairment reaching its severity and dementia. The purpose of this research was to define the existence of depression, identify the degree of cognitive impairment in older adults of the gerontological center "Nuevo Amanecer" in the city of Zumba according to sex, and describe the relationship between these variables. It had a quantitative, prospective, cross-sectional cohort approach, with a sample of 53 patients who met the inclusion and exclusion criteria, to whom the Yesavage geriatric depression scale and the brief neuropsychological evaluation in Spanish (NEUROPSI) were applied, obtaining that 47. 20% (n=25) showed mild depression (18.90% (n=10) males and 28.30% (n=15) females) and 20.70% (n=11) established depression (13.20% (n=7) males, 07.50% (n=4) females). Regarding the degree of cognitive impairment 35.90% (n=19) manifested severe degree, 20.80% (n=11) women and 15.10% (n=8) men, 18.90% (n=10) moderate predominating in women with 15.10% (n=8) and 20.70% (n=11) mild prevailing in women with 11. 30% (n=6). Statistical significance between the variables was evidenced by a value of p=0.0047, it was observed that older adults who presented established depression also presented severe or moderate cognitive impairment.